The Ground Surface Hemiptera (True Bugs) in The Muhammad Sabki City Forest Area of Jambi City - Suhanda, Robet; Wulandari, Tia; Sakinah, Audriella Nadine; Putra, DheanPrimanda (Biospecies, 2025)
Muhammad Sabki City Forest Park (THKMS) is one of the Green Open Spaces in Jambi City, which serves as a natural habitat for various species of flora and fauna, both naturally and through captivity programs. One group of organisms that can be found in the THKMS area is soil surface insects, one of them is the true bug (Order Hemiptera). Hemiptera is an order whose organisms that play a role as phytophagous pests that harm plants in the agricultural sector and also as decomposers in the process of soil material overhaul. In addition to playing a role as phytophages, insects in the Hemiptera order also act as predators in the environment by piercing and sucking their prey, thus reducing the population of plant pests as natural enemies. This study aims to identify the types of soil surface Hemiptera in THKMS. The collection of Hemiptera insect samples was carried out passively using pitfall traps . Based on the identification results, the soil surface Hemiptera species collected were Lisarda rhypara, L. annulata, and Opistoplatys sp., all of them belong to the suborder Heteroptera and included to family Reduviidae. Morphologically, Hemiptera insects have a piercing-sucking mouth type and lack of cerci. Members of the Reduviidae family are known as "Assassin bugs," which are nocturnal. Reduviidae members are large in size and naturally aggressive, making them predators of several other insects. The Reduviidae family is cosmopolitan and has a wide distribution. Ecologically, the insect species found are predators, characterized by their piercing-sucking mouthparts.